1986
DOI: 10.1007/bf00251036
|View full text |Cite
|
Sign up to set email alerts
|

Differential subcellular localization of ACTH and ?-MSH in corticotropes of the rat anterior pituitary

Abstract: Specific antisera to alpha-melanotropin (alpha-MSH) and corticotropin (ACTH 1-39) were used to obtain immunocytochemical evidence for the differential localization of alpha-MSH and ACTH in the secretory granules of corticotropes of rat anterior pituitary. The specificity of the antisera was established by binding 131I-labeled alpha-MSH and ACTH 1-39 to their respective antisera. Double-labeling immunocytochemistry (for alpha-MSH, ferritin; for ACTH, colloidal gold) was performed. Some secretory granules were l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 22 publications
0
22
0
Order By: Relevance
“…The presence of a-MSH did not result from contamination of the PD with NIL tis sue or of residual NIL a-MSH on the HPLC column, since the ratio between the three a-MSH forms was different between the two tissues. The processing of ACTH into desacetylated a-MSH in particular has also been demonstrated in the corticotropes of other vertebrates (Tanaka and Kurosomi, 1986;Dores et al, 1993). A function of this process is unclear, but it has been observed to be most prominent during fetal/ neonatal developmental stages (Dores et al, 1993) and to be under regulation by CRH (Iturriza and Ferese-Spinelli, 1991).…”
Section: Discussionmentioning
confidence: 93%
“…The presence of a-MSH did not result from contamination of the PD with NIL tis sue or of residual NIL a-MSH on the HPLC column, since the ratio between the three a-MSH forms was different between the two tissues. The processing of ACTH into desacetylated a-MSH in particular has also been demonstrated in the corticotropes of other vertebrates (Tanaka and Kurosomi, 1986;Dores et al, 1993). A function of this process is unclear, but it has been observed to be most prominent during fetal/ neonatal developmental stages (Dores et al, 1993) and to be under regulation by CRH (Iturriza and Ferese-Spinelli, 1991).…”
Section: Discussionmentioning
confidence: 93%
“…In rat pituitaries, mammotrophs in the central region of the anterior pituitary stimulate PRL secretion and cell proliferation in response to α-MSH (Porter and Frawley, 1992). During the postnatal ontogeny period, α-MSH is clearly localized in the mouse anterior pituitary (Marcinkiewicz et al, 1993), while corticotroph subpopulations in adult female rat pituitaries produce α-MSH as described above (Tanaka and Kurosumi, 1986). Therefore, it is possible that α-MSH produced in the anterior pituitary controls the functioning of mammotrophs in a paracrine manner.…”
Section: Proopiomelanocortin (Pomc) Peptidesmentioning
confidence: 87%
“…α-MSH is mainly produced in the intermediate lobes, while a light and electron microscopic study revealed that it is also produced in the corticotrophs of adult female rat pituitaries (Tanaka and Kurosumi, 1986). α-MSH stimulated PRL secretion and the proliferation of mammotrophs through melanocortin-3 receptor (MC3-R) (Morooka et al, 1998;Matsumura et al, 2003).…”
Section: Proopiomelanocortin (Pomc) Peptidesmentioning
confidence: 99%
“…This enzyme, plus increased carboxypeptidase activity (or a specific glucocorticoid-sensitive enzyme), may thus be crucial in the generation of NacaEP, the principal acetylated species produced in the abattoir/glucocorticoid-treated anterior pituitaries. Another possibility is the differential accumulation of the various POMC products in subpopulations of POMC-producing cells (19,20), which may be sensitive to different regulatory mechanisms (2 I), perhaps reflecting a heterogeneous distribution of releasable pools, as suggested by Ham and Smyth (9,14). The possibility also remains that these processing effects simply represent a change in intracellular steady state.…”
Section: Discussionmentioning
confidence: 99%